Mechanisms of Cardiovascular Changes of Phototherapy in Newborns with Hyperbilirubinemia - Javorka, K; Maťašová, K; Javorka, M; Zibolen, M (Physiological research, 2023)
During phototherapy of jaundiced newborns, vasodilation occurs in the skin circulation compensated by vasoconstriction in the renal and mesenteric circulation. Furthermore, there is a slight decrease in cardiac systolic volume, and blood pressure, as well as an increase in heart rate and discrete changes in the heart rate variability (HRV). The primary change during phototherapy is the skin vasodilation mediated by multiple mechanisms: 1) Passive vasodilation induced by direct skin heating effect of the body surface and subcutaneous blood vessels, modified by myogenic autoregulation. 2) Active vasodilation mediated via the mechanism provided by axon reflexes through nerve C-fibers and humoral mechanism via nitric oxide (NO) and endothelin 1 (ET-1). During and after phototherapy is a rise in the NO:ET-1 ratio. 3) Regulation of the skin circulation through the sympathetic nerves is unique, but their role in skin vasodilation during phototherapy was not studied. 4) Special mechanism is a photorelaxation independent of the skin heating. Melanopsin (opsin 4) - is thought to play a major role in systemic vascular photorelaxation. Signalling cascade of the photorelaxation is specific, independent of endothelium and NO. The increased skin blood flow during phototherapy is enabled by the restriction of blood flow in the renal and mesenteric circulation. An increase in heart rate indicates activation of the sympathetic system as is seen in the measures of the HRV. High-pressure, as well as low-pressure baroreflexes, may play important role in these adaptation responses. The integrated complex and specific mechanism responsible for the hemodynamic changes during phototherapy confirm adequate and functioning regulation of the neonatal cardiovascular system, including baroreflexes.
Keywords: srdce; Nitric Oxide; Hyperbilirubinemia; Vasodilation; novorozenec; hyperbilirubinemie; vazodilatace; lidé; oxid dusnatý; Heart; Phototherapy; fototerapie; kůže; Skin; Humans; Infant, Newborn